2000
DOI: 10.3758/bf03205550
|View full text |Cite
|
Sign up to set email alerts
|

Tactile perception in blind Braille readers: A psychophysical study of acuity and hyperacuity using gratings and dot patterns

Abstract: It is not clear whether the blind are generally superior to the sighted on measures of tactile sensitivity or whether they excel only on certain tests owing to the specifics of their tactile experience. Wecompared the discrimination performance of blind Braille readers and age-matched sighted subjects on three tactile tasks using precisely specified stimuli. Initially, the blind significantly outperformed the sighted at a hyperacuity task using Braille-like dot patterns, although, with practice, both groups pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
123
4
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(146 citation statements)
references
References 63 publications
18
123
4
1
Order By: Relevance
“…Despite some experience-based superiority in performing some tactile discrimination tasks (Stevens et al, 1996;Grant et al, 2000;Van Boven et al, 2000), early blind people are also less adept at tasks requiring mental rotation of tactile stimuli (Sathian, 2000) or visuospatial and pictorial imagery (Aleman et al, 2001). These deficits might indicate limitations imposed by haptic experience when the tactile modality is the only sense available to cross-modal visual areas responsible for mental imagery (Aleman et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Despite some experience-based superiority in performing some tactile discrimination tasks (Stevens et al, 1996;Grant et al, 2000;Van Boven et al, 2000), early blind people are also less adept at tasks requiring mental rotation of tactile stimuli (Sathian, 2000) or visuospatial and pictorial imagery (Aleman et al, 2001). These deficits might indicate limitations imposed by haptic experience when the tactile modality is the only sense available to cross-modal visual areas responsible for mental imagery (Aleman et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…The roughness percept reflects the properties of the surface touched in interaction with the manner in which Studies have typically shown a decline in spatial acuity on the fingertip with increasing age for both sighted and blind individuals (e.g., Goldreich & Kanics, 2003;VegaBermudez & Johnson, 2004); for a more detailed summary, see Table 1 in Legge, Madison, Vaughn, Cheong, and Miller (2008). Studies that have used more recent psychophysical procedures further reveal that tactile spatial acuity in blind subjects is typically better than in sighted subjects who have been matched for age (but see Grant, Thiagarajah, & Sathian, 2000).…”
Section: Haptic Perception Of Object and Surface Propertiesmentioning
confidence: 99%
“…Van Boven et al (2000) tested 15 early blind Braille readers and 15 sighted subjects, manually applying the gratings to the index and middle fingers of both hands, and concluded that the blind subjects were superior to the sighted on all four fingers. Grant et al (2000) tested 15 early blind Braille readers, 9 late blind Braille readers, and 25 sighted subjects, manually applying the gratings to the index fingers of both hands, and concluded that the three groups did not differ on either finger. Our finding of superior acuity in blind subjects confirms that of Van Boven et al (2000); it is also consistent with Stevens et al (1996), who found superior performance in blind subjects on several nongrating measures of passive tactile acuity.…”
Section: Comparison With Previous Psychophysical Studiesmentioning
confidence: 99%
“…Auditory spatial localization is reportedly enhanced in blindness (Lessard et al, 1998;Röder et al, 1999), but whether blind people have enhanced tactile acuity has long been controversial (Axelrod, 1959;Warren, 1978;Hollins, 1989;Pascual-Leone and Torres, 1993;Stevens et al, 1996;Grant et al, 2000;Van Boven et al, 2000). The tactile perception of blind and sighted subjects has been compared on a variety of active (finger scanning) and passive (finger stationary) paradigms, but accurate assessment of tactile acuity is technically challenging.…”
Section: Introductionmentioning
confidence: 99%